2004
DOI: 10.1590/s0004-28032004000400006
|View full text |Cite
|
Sign up to set email alerts
|

Liver resection: 10-year experience from a single Institution

Abstract: BACKGROUND: Liver resection constitutes the main treatment of most liver primary neoplasms and selected cases of metastatic tumors. However, this procedure is associated with significant morbidity and mortality rates. AIM: To analyze our experience with liver resections over a period of 10 years to determine the morbidity, mortality and risk factors of hepatectomy. PATIENTS AND METHODS: Retrospective review of medical records of patients who underwent liver resection from January 1994 to March 2003. RESULTS: E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
1
5
0
2
Order By: Relevance
“…Our results showed that the rates of mortality and morbidity after trisectionectomies were comparable to those of major resections performed in our department in the same period. Besides, our results were similar to mortality and morbidity rates quoted in patients undergoing liver resection in literature, even for less extensive hepatectomies [6,9,26,27]. Liver failure was the cause of death in both patients of TR group; besides, liver failure represented the only morbidity significantly higher in TR group compared with MH group.…”
Section: Discussionsupporting
confidence: 88%
“…Our results showed that the rates of mortality and morbidity after trisectionectomies were comparable to those of major resections performed in our department in the same period. Besides, our results were similar to mortality and morbidity rates quoted in patients undergoing liver resection in literature, even for less extensive hepatectomies [6,9,26,27]. Liver failure was the cause of death in both patients of TR group; besides, liver failure represented the only morbidity significantly higher in TR group compared with MH group.…”
Section: Discussionsupporting
confidence: 88%
“…8 Diseased livers such as steatotic or fibrotic livers may be the most vulnerable to temporary interruption of blood flow. [9][10][11] Surgical techniques are known to protect liver cells against subsequent sustained ischemia in cases of ischemic-reperfusion injury in animal models 12 as well as in humans. 11,13 Currently, ischemic preconditioning with continuous clamping, but also intermittent portal triad clamping (cycles of 15 minutes of ischemia followed by 5 minutes of reperfusion) are the only clinically established protective strategies against liver injury due to prolonged ischemia.…”
Section: Miniabstractmentioning
confidence: 99%
“…However, the first successful liver resection was performed in 1888 by Langenbuch and the technique of vascular control, with great improvement on the procedure, was introduced by Pringle in 1908 1 . In the last decades, the surgical safety increased considerably because of new techniques, new equipment and materials, reducing the morbidity and mortality of patients submitted to hepatectomy 2 .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%